The double-edged sword role of hydrogen sulfide in hepatocellular carcinoma - Zhao, Huijie; Zhang, Yanting; Fu, Xiaodi; Chen, Chaoren; Khattak, Saadullah; Wang, Honggang (Frontiers in Pharmacology, 2023)
With an increasing worldwide prevalence, hepatocellular carcinoma (HCC) is the most common primary malignant tumor of the liver in the world. It is also the primary reason for cancer-related death in the world. The pathogenesis of HCC is complex, such as DNA methylation changes, immune regulatory disorders, cell cycle disorders, chromosomal instability, and so on. Although many studies have been conducted on HCC, the molecular mechanisms of HCC are not completely understood. At present, there is no effective treatment for HCC. Hydrogen sulfide(H2S) has long been regarded as a toxic gas with the smell of rotten eggs, but recent studies have shown that it is an important gasotransmitter along with carbon monoxide(CO) and nitric oxide(NO). Increasing evidence indicates that H2S has multiple biological functions, such as anti-inflammation, anti-apoptosis, anti-oxidative stress, and so on. Recently, a lot of evidence has shown that H2S has a "double-edged sword" effect in HCC, but the mechanism is not fully understood. Here, we reviewed the progress on the role and mechanism of H2S in HCC in recent years, hoping to provide the theoretical reference for future related researches.